The potential of the antiplatelet agent ticagrelor as a new antibacterial agent - Ueda, Risa; Kataoka, Hiromitsu (Revista Médica de Risaralda, 2023)
The number of deaths caused by drug-resistant bacteria is expected to increase in the future, and there is a need to develop new antimicrobial agents. Recently, the antiplatelet drug ticagrelor has been reported to have promising antibacterial properties. The purpose of this review is to analyze articles and case reports that describe the antimicrobial action of ticagrelor. Ticagrelor was found to have antibacterial reactions against Gram-positive bacteria, including drug-resistant and spore-forming bacteria, while no effect was observed against Gram-negative bacteria. In this paper we discuss a new potential antimicrobial agent, ticagrelor.